The Role of Nursing Leadership Delegation in Managing Workload and Staff Shortage During Crisis: A Systematic Review - Abdu Mohammed Hassan; Hamad Khalfan Hussain Shagrey; Hind Shoey Moh’dhakami; Orjuwan Abdullah Ali Sahli; Ghusun Abdullaha Sahli; Mohammed Yahya Hussein Meshilwe; Eman Shoey Moh’dhakami; Naseem Mossa Gasem Jaran; Rawda Mohmmed Ahmed Qussiry; Norah Mohamed Akkam; Wejdan Sonbol Hadi Mubark; Norah Abdu Siddiq Awam (International Journal of Medical Toxicology and Legal Medicine, 2024)
Due to the continuous need to reduce costs and maintain or improve the quality of care, nursing leadership delegation is an essential managerial role in managing work and addressing staff shortages. This problem is particularly evident in times of crisis, in which the number of patients is outstripping the number of available nurses, for example, during pandemics or natural catastrophes. Nursing leadership delegation involves the distribution of tasks among nursing staff, allowing other nurses to assume increasing responsibility and providing the tools, support, and guidance that delegating nurses require. Despite its importance, the role of nursing leadership delegation in managing workload and staff shortages during crises is an under-researched area. The aim of this systematic review is to provide a thorough description of the role of nursing leadership delegation in the management of nursing workload and nurse staffing shortages during crisis situations. The specific objectives are to examine the concept of the nursing leadership role and nursing leadership delegation, how it is distinguished from other leadership roles during crisis situations, and to search for evidence related to suggesting how the role of management can allow other nursing staff to assume increasing responsibility.